Pengaruh Atribut Toko terhadap Keputusan Pembelian di Toko Ritel Alfamart Cabang Sidoarjo - Dinata, endric Sayogo; Maduwinarti, ayun; Andayani, Sri (Jurnal Dinamika Administrasi Bisnis, 2017)
With so many retail companies that grow around Sidoarjo region, especially in the area of Sidoarjo branch Alfamart, requires customers to choose one as a retail shop. If the views of factors - factors that exist, it is in the shop Alfamart it is still not optimal in increasing consumer purchasing decisions disbandingkan with retail tokko that are nearby. This study aimed to determine whether the location, price and service influence on purchase decisions in Alfamart Branch of Sidoarjo and analyze the most dominant factor in influencing purchasing decisions on purchase decisions Alfamart Branch of Sidoarjo. The population in this study are those who have visited and shopped at the store Alfamart Branch of Sidoarjo. Samples taken as many as 88 respondents using Convenience Sampling techniques (sampling intentionally). Based on the research results, obtained the following regression equation: Y = 4.321 + 0.073 X1 - 0.103 0.091 X2 + X3.There is a positive and significant influence of the independent variables are location and service to the customer's purchase decision dependent variable. And there are no significant negative effects and of the independent variable is the price of the dependent variable purchase decision. Through testing coefficient of determination (R Â²) obtained a value of 0.660 means that the independent variable of location, price and service impact by 66, 0% of the dependent variable purchasing decisions of buyers in Alfamart Branch of Sidoarjo, while 34.0% is influenced by other variables.Keywords: Location, Price, Service and Purchase Decision